If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 = 69 Reorder the terms: 12 + 3x = 69 Solving 12 + 3x = 69 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3x = 69 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = 69 + -12 3x = 69 + -12 Combine like terms: 69 + -12 = 57 3x = 57 Divide each side by '3'. x = 19 Simplifying x = 19
| 11=2(w-2)+2w | | 10b-10=9b | | -5(9p-4)= | | 48n^2-6=-42n | | f^2+g^2=2fg | | -10x+3=-17 | | 3x-9=10x-30 | | 63=3u | | 2x+12=2x-19 | | 3e=27 | | 1/5=10/50 | | 3-18+4m=m | | 10=v-9 | | b-1+4=b-1 | | 16-16xsquared=0 | | 115+24x-5=90 | | 100*y=2.2973 | | 10r+2=3(r+4) | | y-9=-7 | | 6+15n=17n+26 | | m+9=91 | | 4(x+6)=2(7x+1) | | 440=3(w-60)+2w | | x-.22x=506.61 | | 3m+2n=-2 | | 4q=84 | | 11x+5x-103=105 | | 49k+105=1323-21k | | 4p=86 | | 4xb=52 | | Y^2-79=90 | | ln*x+ln*2x=10 |